Cereal Market Performance in Ethiopia : Policy Implications for Improving Investments in Maize and Wheat Value Chains - World Bank (World Bank, Washington, DC, 2018)
The objective of this study is to provide an updated overview on the performance of cereal markets in Ethiopia. Specifically, the study seeks to inform and guide project operations for the Government of Ethiopia (GoE) and the World Bank. First, it aims to inform the government about incentives concerning grain storage before the GoE makes more public investments in storage facilities at the cooperative and union levels. Second, both the GoE and the World Bank need a better understanding of cereal market performance, including the constraints for private sector investment in storage facilities. Further, to respond to increasing demand from the government for more food-based (nonmarket) interventions to provide access to food to the poor instead of market-based (cash or voucher transfers), the PSNP program will need to be better informed about the level and extent of cereal market integration. The report is organized as follows: section two provides an overview of the maize and wheat subsectors. It also summarizes key observations about maize and wheat value chain performance based on a field survey. Section three details the conceptual framework and the empirical strategy to assess the maize and wheat markets performance. Section three presents the empirical model. Section four discusses data and section five presents the empirical results. Finally, the conclusions and policy implications are discussed in section six.